Makna Kerinduan dalam Puisi Karya W.S. Rendra dan Medy Loekito - Agsan, Hanna Zaky; Wulandari, Yosi (ppjbsip, 2022)
The research analysis of comparative literary studies is motivated by two titles of poetry texts that have the same meaning, namely the poem